1975
DOI: 10.1002/j.1537-2197.1975.tb14101.x
|View full text |Cite
|
Sign up to set email alerts
|

Floral Anatomy in the Saxifragaceae Sensu Lato. Iv. Baueroideae and Conclusions

Abstract: This paper presents a description of the floral anatomy and morphology of Bauera rubioides and a general discussion of how the patterns of variation in floral characters among the subfamilies of the Saxifragaceae sensu lato described in this and previous papers correlate with the patterns of variation in other types of characters (i.e., embryology, biochemistry, etc.). Major conclusions are: (1) The Saxifragoideae, including Ribes, forms a rather homogeneous taxon with regard to floral and other characters. (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1975
1975
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Hallier (1901) placed Parnassia with Sarraceniales, then with Saxifragaceae (1903), but again (1908) with Droseraceae and Sarraceniaceae. A separate family was also supported by Takhtajan (1959), Huber (1961) and Bensel & Palser (1975b). Furthermore, serological studies of seed proteins showed no affinity of Parnassia with Saxifragaceae (Grund & Jensen, 1981).…”
Section: Systematics Of Celastralesmentioning
confidence: 73%
“…Hallier (1901) placed Parnassia with Sarraceniales, then with Saxifragaceae (1903), but again (1908) with Droseraceae and Sarraceniaceae. A separate family was also supported by Takhtajan (1959), Huber (1961) and Bensel & Palser (1975b). Furthermore, serological studies of seed proteins showed no affinity of Parnassia with Saxifragaceae (Grund & Jensen, 1981).…”
Section: Systematics Of Celastralesmentioning
confidence: 73%
“…(Bentham & Hooker, 1862–1867; Eichler, 1878; Engler, 1930), or Escalloniaceae (Hutchinson, 1969). Bensel & Palser (1975a, b) stated that Ixerba is not related to Brexia based on floral structure, resembling more that of Escalloniaceae. Thorne (2000) placed Ixerba in Escalloniaceae, and Brexiaceae in Celastrales, but Takhtajan (1997) in Ixerbaceae of Brexiales (Celastranae).…”
Section: Floral Structure and Systematicsmentioning
confidence: 99%
“…Chrysosplenium L. (Saxifragaceae) is a genus of small succulent and fragile herbs characterized by tetramerous flowers with petaloid sepals (Bensel and Palser 1975, Soltis 2007, Soltis et al 2001). It is composed of approximately 70 species, mainly distributed in temperate regions of the Northern Hemisphere, except for two disjunctive species in Chile (Hara 1957, Spongberg 1972, Pan 1986, Ye and Zhang 1994, Wakabayashi and Takahashi 1999, Han and Kang 2012, Bhaumik 2014, Kim and Kim 2015, Liu et al 2016, Kim et al 2018, Wakabayashi et al 2018).…”
Section: Introductionmentioning
confidence: 99%